Crescimento e relações entre variáveis em progênies e cultivares crioulas de milho - Deprá, Marta Stochero (2014)
Corn is one of the crops that produce more in the world; it has a wise geographic distribution. It happens because of the big genetic variability present, including in creole cultivates which they are normally produced in small properties. The main goals of this study were to evaluate the growing and the relation between the seeds labile, grown plants and of the Amarelão creole cultivates, Lombo Baio and Oito carreiras as well as the maternal half-brothers progenies from these cultivates. The experiment happened in Santa Maria, RS in the agricultural year of 2012/2013, in block delineations aimlessly with four repetitions and portions constituted by two lines of five meters to the creole cultivates and a lattice delineation with constituted portions one line of five meters with a space of 0,2m and between lines of 0,9m. For an analysis of the growing plants was accomplished five evaluations of the plant height and leaves numbers by plant and the growing curves were adjusted by logistic model because of the thermal sum accumulated. To analyze the canonical correlation were evaluated: mass, length, width, and seeds thickness; plant height, ear insertion height, thatch diameter and leaves number by plant for grown plants, grain weights, row numbers and grain numbers by rows to the production. The logistic model was adequate to the growing curve adjusts to progenies of maternal half-brothers and corn creole cultivates. Amarelão creole cultivates, Lombo baio and Oito carreiras present the highest plant and the biggest number of leaves by plant in comparison to concerning progenies of maternal half-brothers. The most important canonical correlations were gotten between labile groups of the grown plant and production. The labile plant height and thatch diameter were the most favorable the grain production.